Análises físico-químicas de ração contendo folhas de Estévia rebaudiana e avaliação de propriedades funcionais em ratos diabéticos - Bongiovani, Gislene (2015)
Diabetes mellitus (DM) is one of the most common chronic diseases nowadays. Diabetic people can benefit from diets which helps on the glycemic and lipid control. The Stevia rebaudiana, native plant from the border region between Brazil and Paraguay is a source of non-caloric natural sweeteners and the empirical knowledge of native Paraguayan that diabetic who were making use of stevia tea presented improvement in glycemic levels, stimulated the investigation about possible hypoglycemic and antidiabetic properties of the full extract or isolated products of this plant were found in the last few decades, but has almost no studies with the full leaf. In this work was investigated the hypothesis that diabetic rats fed with ration supplemented with stevia rebaudiana leaves could present better metabolic control. Were used streptozotocin diabetic wistar male rats fed with ration containing 2% of stevia rebaudiana leaves (seminal variety SteviaUEM-13) dryed and milled for four weeks. The obtained results showed that the supplementation improved the glycemic control ( fast glycemia reduction and liver glycogen rise ) and lipid control ( reduction of triglycerides and total cholesterol on the blood concentration) on diabetic rats, without causing changes in food intake and body weight gain.